Double-balloon endoscopy versus magnet-imaging enhanced colonoscopy for difficult colonoscopies, a randomized study - Suzuki, T.; Matsushima, M.; Tsukune, Y.; Fujisawa, M.; Yazaki, T.; Uchida, T.; Gocyo, S.; Okita, I.; Shirakura, K.; Sasao, K.; Saito, T.; Sakamoto, I.; Igarashi, M.; Koike, J.; Takagi, A.; Mine, T. (Endoscopy, 2012)
Background and study aims: Studies have estimated that failure of cecal intubation occurs with conventional colonoscopy in up to 10 % of cases. Double-balloon endoscopy (DBE) systems, magnetic endoscope imaging (MEI), and transparent cap have been shown to improve success rates for colonoscopy. This study evaluated the utility of DBE for complete examination of the colon compared with MEI plus cap (MEI-Cap) after incomplete or technically difficult colonoscopy in a randomized comparative manner.Patients and methods: A total of 94 patients with incomplete or technically difficult colonoscopy were randomly assigned to receive either DBE (n = 47) or colonoscopy with MEI–Cap (n = 47). The primary end point was cecal intubation rate within 30 minutes. Secondary end points included intubation time, pain score using a visual analog scale, abdominal pressure attempts, doses of sedative medication, and changes in patient position during colonoscopy. Results: Patient characteristics were comparable in both groups. Cecal intubation rate within 30 minutes was significantly higher for DBE (45 /47, 95.7 %) than for MEI–Cap (34 /47, 72.3 %) (P = 0.0049). Mean time to reach the cecum was significantly lower in the DBE group (13.0 ± 5.3 minutes) than in the MEI–Cap group (16.4 ± 4.8 minutes; P = 0.0003). No complications were encountered in either group. Conclusion: DBE is more useful for complete examination of the colon than MEI–Cap in patients with incomplete or technically difficult colonoscopy.